New archaeological and archaeometric data on Sicilian wine amphorae in the Roman period (1st to 6th century AD): Typology, origin and distribution in selected western Mediterranean contexts - Franco, Carmela; Capelli, Claudio (Rei Cretariae Romanae Fautorum Acta, 2015)
This contribution will attempt to present an initial assessment of Sicilian wine amphorae through the analysis of a more expanded catalogue of forms and fabric data, with the primary aim of establishing amphorae origins.